2009
DOI: 10.1007/s00125-009-1473-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose variability does not contribute to the development of peripheral and autonomic neuropathy in type 1 diabetes: data from the DCCT

Abstract: Abbreviations EMG Electromyography MAGE Mean amplitude of glycaemic excursionsTo the Editor: While it is suggested that, in addition to hyperglycaemia, glucose variability can contribute to the severity and development of diabetic neuropathy [1], it is not related to the development of retinopathy and nephropathy in type 1 diabetes [1,2]. To determine any additional effect of glucose variability-above that assessed by HbA 1c and mean glucose-on peripheral and autonomic diabetic neuropathy, we used the datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 11 publications
3
55
0
Order By: Relevance
“…In this issue of Diabetologia, Monnier et al report an influence of insulin therapy on urinary 8-iso-PGF2α excretion in a cross-sectional setting and provide data from small groups of type 2 diabetes patients started on either insulin therapy or receiving additional OHA [7]. The results from this study are particularly interesting, as they imply an independent effect of insulin therapy on oxidative stress and could help explain some recent observations on glucose variability and the development of late complications in clinical trials [8][9][10].In the cross-sectional study, type 2 diabetes patients on OHA were shown to have a ∼60% increased urinary 8-iso-PGF2α excretion compared with type 1 or type 2 diabetes patients treated with insulin. 8-Iso-PGF2α excretion in the latter two groups did not differ significantly compared with non-diabetic controls.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In this issue of Diabetologia, Monnier et al report an influence of insulin therapy on urinary 8-iso-PGF2α excretion in a cross-sectional setting and provide data from small groups of type 2 diabetes patients started on either insulin therapy or receiving additional OHA [7]. The results from this study are particularly interesting, as they imply an independent effect of insulin therapy on oxidative stress and could help explain some recent observations on glucose variability and the development of late complications in clinical trials [8][9][10].In the cross-sectional study, type 2 diabetes patients on OHA were shown to have a ∼60% increased urinary 8-iso-PGF2α excretion compared with type 1 or type 2 diabetes patients treated with insulin. 8-Iso-PGF2α excretion in the latter two groups did not differ significantly compared with non-diabetic controls.…”
supporting
confidence: 51%
“…Targeting of postprandial glucose values in the STOP-NIDDM trial did indeed reduce the development of diabetes, hypertension and cardiovascular events [25,26]. Yet, glucose variability was not identified as a risk factor for microvascular disease or neuropathy in the DCCT study of type 1 diabetes patients treated with insulin [8,10], while the HEART-2D trial failed to show that prandial insulin therapy is superior to a basal regimen in the prevention of secondary cardiovascular events [9]. These considerations and the observation that insulin therapy improves oxidative stress to levels observed in healthy non-diabetic patients [7] prompts speculation that glucose variability does not contribute significantly to the progression of vascular complications in diabetes patients on insulin treatment in whom insulin itself could elicit beneficial effects on the vessel.…”
mentioning
confidence: 99%
“…Of note, previous reports suggested that acute oscillations of blood glucose have a more deleterious effect on endothelial function than constant hyperglycemia in patients with type 2 diabetes (T2DM) (3,4), which may support the concept that glycemic variability can induce oxidative stress and thereby affect the pathophysiologic pathways through which diabetes complications arise (5). However, although some studies have reported that increased glycemic variability may be associated with the incidence of diabetic retinopathy (6,7), diabetic neuropathy (8), and coronary artery calcification (9) in patients with T2DM and type 1 diabetes (T1DM), other studies have not supported this association (10)(11)(12). Nevertheless, although its relevance to vascular complications remains uncertain (13), at a given level of glycemia, increased glucose variability raises the risk of hypoglycemia (14)(15)(16) and, hence, is clinically important.…”
mentioning
confidence: 98%
“…19 However, recent independent analyses of DCCT glycemia data performed by the DCCT coordinating center have contradicted these findings and reported that the SD of glucose does not relate to the progression of microvascular complications in general. 20,21 Similarly, Siegelaar et al 21 used SD and MAGE to evaluate the relationship between DCCT glucose data and complications, concluding that glucose variability as assessed by these measures does not contribute to the development of peripheral and autonomic neuropathy.…”
Section: Rawlings Et Almentioning
confidence: 99%